2023
DOI: 10.1128/spectrum.03078-22
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of 15 Novel Dense Granule Proteins in Toxoplasma gondii Using the CRISPR-Cas9 System

Abstract: Dense granule proteins (GRAs) play important roles in Toxoplasma gondii pathogenicity. However, the functions of many putative GRAs have not been elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…We show that GRA83 is secreted into the vacuole in both tachyzoites and bradyzoites, suggesting that it functions in both lifecycle stages. While this manuscript was in preparation, another group also demonstrated that the epitope-tagged protein is secreted into the vacuole in tachyzoites ( 54 ). Together with the hyperLOPIT prediction ( 34 ), which tends to be reliable for dense granule proteins, these results confirm that GRA83 is indeed a secreted GRA protein.…”
Section: Discussionmentioning
confidence: 98%
“…We show that GRA83 is secreted into the vacuole in both tachyzoites and bradyzoites, suggesting that it functions in both lifecycle stages. While this manuscript was in preparation, another group also demonstrated that the epitope-tagged protein is secreted into the vacuole in tachyzoites ( 54 ). Together with the hyperLOPIT prediction ( 34 ), which tends to be reliable for dense granule proteins, these results confirm that GRA83 is indeed a secreted GRA protein.…”
Section: Discussionmentioning
confidence: 98%
“…The CRISPR-Cas9 mediated homologous gene recombination was used to delete the had2a gene in the wild-type RH strain [ 23 ]. The CRISPR plasmid pSAG1::CAS9-U6::Sg HAD2a and homologous dihydrofolate reductase (DHFR) drug-selective plasmid were constructed.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate the expression and localization of ZFPs in the tachyzoite stage of the RH strain, we performed C-terminal endogenous tagging for eight ZFPs. CRISPR plasmid targeting the 3 -untranslated region (3 -UTR) of the zfp gene was obtained as previously described [17]. A short homology fragment containing 6 × HA tag products and DHFR fragments was amplified from the pLIC-6×HA-DHFR plasmid using specific primers located near the SgRNA at the 3 end of the corresponding zfp gene.…”
Section: Construction Of Epitope Tagging Strainsmentioning
confidence: 99%